Criminal Law Policy in Stopping Investigations in the Taxation - Dadang Sumarna; Dey Ravena; Dini Dewi Herniati; Aji Mulyana (Borong Newinera Publisher, 2022)
Taxes are a source of state income obtained from community contributions for the sustainability of the State, but in reality there are elements of the community who do not carry out their obligations as taxpayers, even misuse the money from the tax proceeds for personal interests which result in state losses, therefore The author aims to examine and analyze more deeply about how criminal law policies stop investigations in the field of taxation, because the Ministry of Finance regulations do not regulate that. As for the conclusion case this should go to court so as not to violate the provisions, must go through a court decision and be acquitted by a court decision so that it has legal force.